Identification of a major QTL-controlling resistance to the subtropical race 4 of Fusarium oxysporum f. sp. cubense in Musa acuminata ssp. malaccensis - Chen, A.; Sun, J.; Martin, G.; Gray, L.A.; Hřibová, E.; Christelova, P.; Yahiaoui, N.; Rounsley, S.; Lyons, R.; Batley, J.; Chen, N.; Hamill, S.; et al. (MDPI, 2023)
Vascular wilt caused by the ascomycete fungal pathogen Fusarium oxysporum f. sp. cubense (Foc) is a major constraint of banana production around the world. The virulent race, namely Tropical Race 4, can infect all Cavendish-type banana plants and is now widespread across the globe, causing devastating losses to global banana production. In this study, we characterized Foc Subtropical Race 4 (STR4) resistance in a wild banana relative which, through estimated genome size and ancestry analysis, was confirmed to be Musa acuminata ssp. malaccensis. Using a self-derived F2 population segregating for STR4 resistance, quantitative trait loci sequencing (QTL-seq) was performed on bulks consisting of resistant and susceptible individuals. Changes in SNP index between the bulks revealed a major QTL located on the distal end of the long arm of chromosome 3. Multiple resistance genes are present in this region. Identification of chromosome regions conferring resistance to Foc can facilitate marker assisted selection in breeding programs and paves the way towards identifying genes underpinning resistance.